Quality Assessment of Active Substances that Demonstrate Sedative Effect of #x201C;Flegmen#x201D; Syrup (Global Journal of Medical Research, 2022)
As a result of the research, the amino acid and elemental composition of #x201C;Flegmen#x201D; syrup was determined, and it was found that the syrup contains 18 amino acids and 57 macro and micro elements. The accumulation in #x201C;Flegmen#x201D; syrup of a significant number of amino acids and useful minerals, along with active biologically active groups (flavonoids, saponins), allows us to objectively consider it as a valuable source of an effective sedative.
Keywords: flegmen; amino acids; regel#x2019; s gooseberry; turkestan motherwort; peppermint; high performance liquid chromatography